Technique and results of primary resection of acute colon cancer - Praderi, Raúl C (Cirugía del Uruguay, 2021)
An analysis is made of the technique employed in the surgery of acute cases of cancer in the colon with occlusion or perforation. Statistics of 33 cases on whiéh surgery was performed in the acute .phase t21 of the left and 12 of the right side) are summarized. Total operatory mortality rate was 6 % with O % for left side cancers. For this and other reasons, it is considered advisable to resect complicated cancers of the colon, in the acute phase.